LINEAR MEASUREMENT OF THE CONDYLE POSITION IN HIV-INFECTED CHILDREN AND ADOLESCENTS - Lusi Epsilawati; Ria N.Firman; Irna Sufiawati; Norlaila Sarifah; Indra Gunawan (FKG Unlam, 2020)
Background: The incidence of HIV had recently increased rapidly. People infected with HIV were required to take anti-viral drugs. The severity of HIV also contributes to a decrease in bone mineral density due to taking antiviral drugs. Decreased bone density in people with HIV was a chronic disease due to the long-term use of drugs. TMD in people with HIV was often associated with several factors including emotional states such as depression. Patient infected HIV was vulnerable to TMD because it triggers physical and psychological changes. TMD and decreased bone density are common in people with HIV. Researchers hope that later there will be the latest findings that can make patients infected with HIV felt safe to take drugs without worrying about the decline in bone quality. Objective: This study aimed to investigate the value of linear measurement of the condyle position in HIV- infected children and adolescents based on panoramic radiographs in Dental Hospital Padjadjaran University. Methods: This descriptive and cross-sectional method was conducted on panoramic radiographs of HIV-infected children and adolescents since was born. Condyle position was defined by linear measurement using a protractor that divides the condyle 45° of anterior, 90° of superior, and 135° of posterior joint space from a horizontal line. The distance was then measured using a digital caliper. Results: According to linear measurements of the condyle position, all samples had abnormal linear distances in children and adolescents in all gender. The standard range of anterior joint space (Ajs) was 1.3 mm, superior joint space (Sjs) was 2.1 mm, and the posterior joint space (Pjs) was 1.8 mm. The result of this research, the right women condyle sample, the standard distance of the AJS was 0%, SJS was 16%, Pjs was 18%. While the left condyle, the usual range of the AJS was 4%, SJS was 12%, Pjs was 24%. The right men condyle sample, the standard distance of the Ajs was 0%, Sjs was 17.65%, Pjs was 11.76%. While the left condyle, the usual range of the Ajs was 0%, Sjs was 11.76%, Pjs was 5.88%. Conclusions: The abnormal distance measured was found in the condyle position of children and adolescents infected with HIV.